Ibu Kota Nusantara: National Capital Development Policy with the Forest City Concept - Nurron, Ona Martha; Ningrum, Sinta; Pancasilawan, Ramadhan (PERSPEKTIF, 2025)
This study examines the urban governance policy in relocating Indonesia's capital city from Jakarta to Ibu Kota Nusantara, or IKN, in East Kalimantan. It was driven by Jakarta's problems, such as overpopulation, which limits its capacity to support urban activities. IKN will include biodiversity conservation areas, protected forests, and abandoned mining sites, which require innovative and sustainable urban planning. Furthermore, this study emphasizes creating a bright, green, and sustainable city while preserving 70–75% of the surrounding forest cover. The researcher applies a qualitative method based on a literature review due to the lack of comprehensive secondary data on the ecological and infrastructural conditions of the site. Findings highlight that effective urban governance requires coordinated efforts between central and regional governments, policy harmonization, the integration of digital technologies, and active participation from stakeholders and local communities to ensure environmental and social sustainability in the new capital.